Enhanced 3-Sulfanylhexan-1-ol Production in Sequential Mixed Fermentation with Torulaspora delbrueckii/Saccharomyces cerevisiae Reveals a Situation of Synergistic Interaction between Two Industrial Strains - Renault, Philippe; Coulon, Joana; Moine, Virginie; Thibon, Cécile; Bely, Marina (Frontiers in Microbiology, 2016)
The aim of this work was to study the volatile thiol productions of 2 industrial strains of Torulaspora delbrueckii and Saccharomyces cerevisiae during alcoholic fermentation (AF) of Sauvignon Blanc must. In order to evaluate the influence of the inoculation procedure, sequential and simultaneous mixed cultures were carried out and compared to pure cultures of T. delbrueckii and S. cerevisiae. The results confirmed the inability of T. delbrueckii to release 4-methyl-4-sulfanylpentan-2-one (4MSP) and its low capacity to produce 3-sulfanylhexyl acetate (3SHA), as already reported in previous studies. A synergistic interaction was observed between the two species, resulting in higher levels of 3SH (3-sulfanylhexan-1-ol) and its acetate when S. cerevisiae was inoculated 24 hours after T. delbrueckii, compared to the pure cultures. To elucidate the nature of the interactions between these 2 species, the yeast population kinetics were examined and monitored, as well as the production of 3SH, its acetate and their related non-odorous precursors: Glut-3SH (glutathionylated conjugate precursor) and Cys-3SH (cysteinylated conjugate precursor). For the first time, it was suggested that, unlike, S. cerevisiae, which is able to metabolize the two precursor forms, T. delbrueckii was only able to metabolize the glutathionylated precursor. Consequently, the presence of T. delbrueckii during mixed fermentation led to an increase in Glut-3SH degradation and Cys-3SH production. This overproduction was dependent on the T. delbrueckii biomass. In sequential culture, thus favouring T. delbrueckii development, the higher availability of Cys-3SH throughout AF (alcoholic fermentation) resulted in more abundant 3SH and 3SHA production by S. cerevisiae